Comparative assessment of trip generation category analysis and regression modelling techniques - Javid Ashenagar (2010)
Thesis (Sarjana Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2010